Strategies to Increase Family Resilience to Disasters Based on Pentahelix Perspectives: A Qualitative Study - Suhari, Suhari; Sulistyono, R Endro; Rahmawati, Primasari Mahardhika; Pebriyanti, Dwi Ochta (Jurnal Berita Ilmu Keperawatan, 2025)
Disasters affect family dynamics as the smallest social unit in society. Disasters that occur in communities have a considerable impact on the lives and property, and mental health of survivors. In addition, it also affects human health, which risks undermining the well-being of families, due to the health problems that can occur. The family's unpreparedness in these tasks can increase the psychological and physical impacts experienced by its members. Therefore, strategies in disaster preparedness are important to reduce the impact. This study aims to explore strategies to improve family resilience in disaster mitigation. The number of interviews is 21 people, consisting of women and men with an average age of 45 years, who have different backgrounds. Including academians, business, community, government, and journalists. The results showed that the strategy to increase family resilience to disaster is based on 5 family tasks from Maglaya's theory, including that families must have a preparedness plan and knowledge about disaster management through education to families about the steps that must be taken before, during, and after a disaster is very helpful in increasing family resilience. The conclusion is that disaster training and simulation programs involving family members have proven effective in building confidence and necessary skills. This research can be concluded that family disaster preparedness depends on good knowledge and planning. Disaster nurses play an important role in education and training, which helps reduce psychological and physical impacts. Thus, community safety and well-being can be improved by exploring strategies to improve family resilience in disaster mitigation